(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: Police personnel perform untiring duties to maintain law and order. The objectives of this study were to assess the physical and mental health status of police personnel in a selected rural subdivision of Bengaluru District. Methods: A cross-sectional study was conducted among 142 police personnel in 7 police stations of the selected rural subdivision using a universal sampling technique. A structured interview schedule was used, which included socio-demographic details, occupational details, anthropometry, blood pressure and blood sugar measurements, Patient Health Questionnaire-9 (PHQ-9) to screen for depression and Perceived Stress Scale (PSS) to identify stress. Results: The mean age of the police personnel was 40.28±10.97 years. Most of the workforce were males (83%). About 68.3% of the studied group were obese. High random blood sugar and high blood pressure values were observed in 5.6% and 48.6% of the personnel who had no previous history of diabetes mellitus and hypertension. The prevalence of mild to severe depression was found to be 36% and that of high stress was 83.1%. Conclusion: The high prevalence of increased blood pressure, obesity, depression and perceived stress warrants the need for routine screening and application of various levels of prevention. Health promotion and improved working conditions can improve their health status.